FAKTOR - FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2015 - Rekno Nitasari, 12.05.52.0063; Wahyudi, Djoko (Students' Journal of Accounting and Banking, 2016)
This study aims at determining the effect of Business Risk, Asset Structure, Company Size, Growth Sales, profitability, liquidity on Capital Structure of Manufacturing Companies Listed on Indonesia Stock Exchange in 22012-2015. This research was conducted in Indonesia Stock Exchange with purposive sampling method with the sampel was taken from the period of 2012-2015. The sample collected includes 112 companies which satisfied some criteria. Analysis tool used multiple regression analysis. The results of the study show that business risk, asset structure, size, growth sale. Profitability ,and  liquidity simultaneously have significantly affect on intellectual capital performance. Result of analysis (t-test) shows that business risk  size and growth sales did not have significantly affect on capital structure. While asset structure affect positife significantly, profitability and likuidity variable negative have significantly affects on capital structure.  Keywords: Capital Structure, Business Risk, Asset Structure, Company Size, Growth Sales, Profitability, Liquidity